Patrones de arquitectura foliar en la subtribu Conceveibinae (Euphorbiaceae) - Murillo Aldana José Carmelo (Caldasia)
The leaf architecture of the species ofthe subtribe Conceveibinae is of great taxonomic value. The pattern of the secondary venation, the number of tertiary veins and the development, arrangement and forms of the areolations are the most useful characters to separate species or groups of species. The areolation is important to separate the sections; in the sect. Gavarretia has imperfect development, while the sect. Conceveiba is incomplete or developed. Venation in Conceveiba is pinnate craspedodromous or pinnate semicraspedodromous, except for C. martiana, C. ptariana, C. maynasensis, and C. pleiostemona where it is actinodromous. The number of pairs of secondary veins is usually less than 10. The tertiary venation is percurrent and frequently oblique. The marginal venation is looped and there are not  intersecondary veins. The largest venation order is between 5° and 7°; in general the veins of 4° and 5° orders are orthogonal. The results ofthis study support as well as inc1usion of Gavarretia and Polyandra in Conceveiba, and the separation of the sections Conceveiba and Gavarretia. La arquitectura foliar de las especies de la subtribu Conceveibinae es de gran valor taxonómico. El patrón de la venación secundaria, el número de venas terciarias y el desarrollo, el arreglo y la forma de las aréolas están entre los caracteres más útiles para separar especies o grupos de especies. Las aréolas tienen importancia para separar las secciones; en la sección Gavarretia tienen desarrollo imperfecto, en tanto que en la sección Conceveiba son incompletas o bien desarrolladas. La venación de las especies de Conceveiba es pinnada craspedódroma b pinnada semicraspedódroma, con excepción de C. martiana, C. maynasensis, C. ptariana y C. pleiostemona en las que es actinódroma. El número de pares de venas secundarias usualmente es menor de 10. La venación terciaria es percurrente y frecuentemente oblicua. La venación marginal es areolada y no hay venas intersecundarias. El mayor orden de venación está entre 5° y 7°, en general las venas de 4° y 5° orden son ortogonales. Los resultados obtenidos del estudio de éstos caracteres apoyan la inclusión de los géneros Gavarretia y Polyandra bajo Conceveiba, único género de la subtribu, y la separación de las secciones Conceveiba y Gavarretia.